Impact of the off-clamp endoscopic robot-assisted simple enucleation (ERASE) of clinical T1 renal tumors on the postoperative renal function: Results from a matched-pair comparison. Issue 6 (June 2018) - Mari, Andrea; Morselli, Simone; Sessa, Francesco; Campi, Riccardo; Di Maida, Fabrizio; Greco, Isabella; Siena, Giampaolo; Tuccio, Agostino; Vittori, Gianni; Serni, Sergio; Carini, Marco; Minervini, Andrea
Abstract: Purpose: To evaluate the surgical and functional outcomes of a matched-paired series of on-clamp vs off-clamp endoscopic robot-assisted simple enucleation (ERASE) and standardized renorraphy in a tertiary referral institution, to search for predictors of functional drop after surgery and to investigate the influence of off-clamp technique in patients presenting these characteristics. Materials and methods: A matched-pair comparison of 120 on-clamp vs 120 off-clamp over 491 patients treated with ERASE was performed. Perioperative and functional outcomes were compared between groups. Results: Patients treated with on-clamp and off-clamp technique had comparable complication and positive surgical margin rate. The off-clamp group had a significantly lower eGFR drop compared to the on-clamp group at 3rd postoperative day (POD) (1% vs 7%, p = 0.0001) and at 30th POD (2.5% vs 9%, p = 0.01) from baseline. This difference lost its statistical significance at 6th month and at last follow-up (median 40 months). At multivariable analysis the Charlson comorbidity index (OR 2.06, p < 0.0001), uncontrolled type 2 diabetes mellitus (OR 4.13, p < 0.001) were independent predictive factors of a >15% eGFR drop from baseline to last follow-up. In a subanalysis over 64 comorbid patients, those patients who underwent off-clamp ERASE had a significantly lower eGFR drop compared to the comorbid counterpart during the whole follow-up. Conclusions: The off-clamp ERASE is a safe surgical technique with a significantly lower renal function drop compared to on-clamp ERASE in the early perioperative time. Patients with comorbidity might represent a subgroup of patients having a functional benefit after off-clamp RAPN even in the long-term period.